Budget planning in Costa Rican public administration: It is implication in national development - Bolaños Garita, Rolando (2015)
The political, legal, administrative and conceptual dimensions that shape and determine budget planning in Costa Rica, understood as the alignment of public budgets to National Development Plan and their breakdowns of second, third and fourth grade; constitute a whole range to be fully aware of Executive, starting with the President (maximum administrator and national ruler) and the Ministers of National Planning and Economic Policy, Finance and makers reach Budgetary Programs as well. Similarly, it should be understood by the Legislature (Legislative Assembly, Standing Committee on Financial Affairs, Commission of Control of Public Expenditure and Income, and Republic´s Comptroller General), in order to exercise appropriate political and administrative control over use of public resources.